Social-economic development of Kazakhstan during the years of World War І (Journal of history, 2020)
мThe article deals with negative consequences of the First World War for Kazakhstan. With Russia’s entry into the war, it faced military-industrial and socio-economic problems. Primarily food products and raw materials were sent to satisfy the needs of the front. Having to provide for the war with raw materials has led to a crisis in the economy of Kazakhstan. Engaging men in rear works resulted in the shortage of labor in the sector traditional for the Kazakhs. «Nomad tent tax» rose. The mass seizure of Kazakh lands had begun. As a result of acts of the tsarist authorities cattle rearing economy went into decline, transforming into foreign elements of farming, such as pig breeding, melon growing, etc. Key words: Kazakhstan, social-economic, land, tax, war.